Rab11‐FIP1 mediates epithelial‐mesenchymal transition and invasion in esophageal cancer. (6th January 2021) - Tang, Qiaosi; Lento, Ashley; Suzuki, Kensuke; Efe, Gizem; Karakasheva, Tatiana; Long, Apple; Giroux, Véronique; Islam, Mirazul; Wileyto, E Paul; Klein‐Szanto, Andres J; Nakagawa, Hiroshi; Bass, Adam; et al.
Abstract: Esophageal squamous cell carcinoma (ESCC) is the most common subtype of esophageal cancer worldwide. The most commonly mutated gene in ESCC is TP53. Using a combinatorial genetic and carcinogenic approach, we generate a novel mouse model of ESCC expressing either mutant or null p53 and show that mutant p53 exhibits enhanced tumorigenic properties and displays a distinct genomic profile. Through RNA‐seq analysis, we identify several endocytic recycling genes, including Rab Coupling Protein (Rab11‐FIP1), which are significantly downregulated in mutant p53 tumor cells. In 3‐dimensional (3D) organoid models, genetic knockdown of Rab11‐FIP1 results in increased organoid size. Loss of Rab11‐FIP1 increases tumor cell invasion in part through mutant p53 but also in an independent manner. Furthermore, loss of Rab11‐FIP1 in human ESCC cell lines decreases E‐cadherin expression and increases mesenchymal lineage‐specific markers, suggesting induction of epithelial–mesenchymal transition (EMT). Rab11‐FIP1 regulates EMT through direct inhibition of Zeb1, a key EMT transcriptional factor. Our novel findings reveal that Rab11‐FIP1 regulates organoid formation, tumor cell invasion, and EMT. Synopsis: Loss of the Rab coupling protein Rab11‐FIP1 fosters disruption of epithelial stratification, tumor cell invasion and EMT in esophageal squamous cell carcinoma. Rab11‐FIP1 is significantly downregulated in esophageal cancer. Rab11‐FIP1 depletion promotes epithelial cell disorganization and tumor cell invasion. Rab11‐FIP1 regulates EMT through direct inhibition of Zeb1. Loss of the Rab coupling protein Rab11‐FIP1 fosters disruption of epithelial stratification, tumor cell invasion and EMT in esophageal squamous cell carcinoma. Abstract : Loss of the Rab coupling protein Rab11‐FIP1 fosters disruption of epithelial stratification, tumor cell invasion and EMT in esophageal squamous cell carcinoma.